Phytosterols and their derivatives: Structural diversity, distribution, metabolism, analysis, and health-promoting uses. (April 2018) - Moreau, Robert A.; Nyström, Laura; Whitaker, Bruce D.; Winkler-Moser, Jill K.; Baer, David J.; Gebauer, Sarah K.; Hicks, Kevin B.
Abstract: Phytosterols (plant sterols) occur in the cells of all plants. They are important structural components that stabilize the biological membranes of plants. Sterols can occur in the "free" unbound form or they can be covalently bound via an ester or glycosidic bond. Since our previous 2002 review on phytosterols and phytosterol conjugates, phytosterol glucosides have been found to be important structural components in the lipid rafts of the plasma membrane of plant cells, where they are thought to be essential to the function of plasma membrane enzymes and perhaps other proteins. Phytosterols also serve as precursors in the synthesis of important bioactive compounds such as steroidal saponins, steroidal glycoalkaloids, phytoecdysteroids, and brassinosteroids. Methods for the analysis of phytosterols range from traditional gas chromatography of free phytosterols to modern sophisticated forms of mass spectrometry which have been used for the new field of sterol lipidomics, sometimes called "sterolomics." Phytosterol-enriched functional foods first appeared about twenty years ago and many clinical studies have confirmed the low density lipoprotein (LDL) cholesterol-lowering properties of various types of phytosterols. In recent years additional clinical studies and more than ten important meta-analyses have provided insights to better understand the cholesterol-lowering and other biological effects of plant sterols.